Enhancement of Trusting Relationship with Motive-Oriented Therapeutic Relationship (MOTR) Approach in Schizophrenia Patients: A Case Report - Fatima, Azrania; Widianti, Efri (Universitas Padjadjaran, 2024)
Building a trusting relationship is the initiation process of the therapeutic communication between nurses and patients. In patients with schizophrenia, Building a trusting relationship is a challenge that is not easy and is often overlooked. If they have no strategies, internal and external factors of both nurses and patients may complicate them in building a therapeutic relationship. One of the techniques of interaction that can be practiced by nurses is Motive-Oriented Therapeutic Relationship. This study uses a case report of one patient with schizophrenia who has auditory hallucination disorder. Interactions were conducted on April 04 - 11, 2023. The intervention used the Motive-Oriented Therapeutic Relationship approach, and the assessment of the trust response used an adaptation of the General Trust Scale instrument. There was a positive response to the patient's trust in the nurse after the Motive-Oriented Therapeutic Relationship experience for 3 days, this was evident from the increase in the average value of the patient's General Trust Scale score from 0.20 to 0.86 whereas the patient was said to have trust if (α =>0.83). Intervention of Motive-Oriented Therapeutic Relationship approach can build BHSP in patients with Schizophrenia and as recommendation it should be carried out together with Plan Analysis (PA) so that the therapeutic relationship is established for optimum psychiatric care.Keywords: Schizophrenia, BHSP, MOTR, GTS.